Comparison of predictive validity of Alvarado score and Lintula score in acute appendicitis in adults - Chandrabose, Karpagavel; Nair, Velayudhan (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Background: Acute appendicitis is still one of the most common emergency encountered in surgical practice at all levels of health care. In resource poor settings, where diagnostic facilities for definitive diagnosis are not available objective clinical scoring systems play an important role in diagnosis and therapeutic decision making. Materials and Methods: To compare the predictive validity of Alvarado score and Lintula score in acute appendicitis in adults. The study was a prospective observational study conducted in the department of general surgery Dr. SMCSI Medical College, Karakonam. Trivandrum, between February to December 2016. A total of 130 subjects aged ≥1 year with symptoms suggestive of acute appendicitis were included. Alvarado and Lintula scores were calculated for all subjects and were compared with histopathology findings. An Alvarado score of ≥7, Lintula score of ≥21 was considered as screening positive. Results: Alvarado score had a sensitivity of 63.15 % (52.31% to 74.00%), specificity of 81.48 % (71.12% to 91.84%). Positive predictive value & Negative predictive value was 82.75% (72.03% to 92.47%) and 61.11% (49.85% to 72.37%) respectively. Diagnostic accuracy was 70.26% (62.95% to 78.58%). Lintula score had a sensitivity of 72.36 % (62.31% to 82.42%), specificity was 88.88 % (80.50% to 97.27%). Positive predictive value & Negative predictive value was 90.16% (82.69% to 97.63%) and 69.56% (58.70% to 80.42%) respectively. Diagnostic accuracy was 79% (95%CI 72.25% to 86.20%). Conclusions: Lintula score is more accurate than Alvarado score in the diagnosis of acute appendicitis.